(untitled) (Philology, 2020)
Virtual learning environments and the Internet lead not only to the enrichment of alternatives for foreign language learning but also require a reconsidering of pedagogy and methodology. This article discusses the application of virtual classrooms in early foreign language learning. The data from a study conducted with 18 preschool teachers of foreign language, who switched to fully remote work in a virtual classroom during the COVID-19 lockdown, are presented. The main findings reveal that the virtual classroom meets the age characteristics of preschool children to a great extent and has the potential to provide a favorable environment for online foreign language acquisition.